A diagnostic accuracy study comparing RNA LAMP, direct LAMP, and rapid antigen testing from nasopharyngeal swabs - Cao, Guojun; Lin, Ke; Ai, Jingwen; Cai, Jianpeng; Zhang, Haocheng; Yu, Yiqi; Liu, Qihui; Zhang, Xinyun; Zhang, Yi; Fu, Zhangfan; Song, Jieyu; Wang, Hongyu; et al. (Frontiers in Microbiology, 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, the early detection and isolation of individuals infected with severe acute respiratory syndrome coronavirus disease 2 (SARS-CoV-2) through mass testing can effectively prevent disease transmission. SARS-CoV-2 nucleic acid rapid detection based on loop-mediated isothermal amplification (LAMP) may be appropriate to include in testing procedures. We used 860 nasopharyngeal specimens from healthcare workers of Huashan Hospital and COVID-19 patients collected from April 7th to 21st, 2022, to assess the clinical diagnostic performance of the LAMP assay marketed by Shanghai GeneSc Biotech and compared it to the result of a rapid antigen test (RAT) head-to-head. Overall, the diagnostic performance of the LAMP assay and RAT were as follows. Comparing the results to the RT-qPCR gold standard, the LAMP assay represented high sensitivity and specificity, especially in testing the extracted RNA samples, as the sensitivity was 70.92% and 92.91% for direct LAMP and RNA-LAMP assay, respectively, and the specificity was 99.86% and 98.33%, respectively. The LAMP assay performed well when detecting specimens with relatively lower Ct values or collected from patients in the early phase (≤7 days) of COVID-19. The combination of LAMP assay and RAT improved diagnostic efficiency, providing new strategies for rapidly detecting SARS-CoV-2. These results suggest the suitability of the LAMP assay for mass screenings of COVID-19 patients in the general population.